AN ANALYSIS OF THE DETERMINANTS OF PADDY AND PULSE DEVELOPMENT IN PAPUA PROVINCE - Demas Wamaerand; Kuntoro Boga Andri (Universitas Sebelas Maret, 2016)
This study aims to: (1) mapping the distribution pattern of the application of agricultural technology innovation specific locations, (2) determine the critical success factors distribution application of agricultural technology innovation specific locations, (3) improvement of distribution patterns and acceleration of the adoption and diffusion of technological innovations to support agribusiness and agroindustrial rice, sweet potatoes and soybeans in Papua. The research activities carried out during March 2011 to February 2014 using three approaches (methods), namely (1) Desk Study on the SL- PTT rice, soybean and sweet potato (2) surveys to obtain quantitative data in three districts purposively selected with 10- 20 respondents, (3) the application pattern of diffusion through the demonstration of quality seeds of rice, corn and soybeans in the BPP or a farmer seed sources in three selected districts.Agronomic data were tabulated and analyzed descriptively. Analysis of the level of efficiency in the application of technology used indicator plots the balance receiptsand fees or analysis of R / C ratio. To measure the success of the application of technological innovations in the plots need to set performance indicators, covering aspects of the use of inputs, processes, outputs, outcomes, benefits and impacts. The results show that the dissemination of technological innovations for the development of location-specific agricultural commodities of rice, corn, soybean and sweet potato, has spread in most regions crop farming development centers in Papua. But only concentrated around the transmigration settlement area. New varieties of soybean plants yielding seeds and rice showed better productivity than the old varieties that have been repeatedly planted by farmers. Yielding varieties of maize is being introduced less developed because it is still constrained by marketing, if the market is readily available, farmers are willing to develop it.